Crisis And Communication Management at Denny's Senayan City SWOT Analysis - Awaloedin, Dipa Teruna; Pradini, Gagih; Fitria, Putri Maulida; Andini, Davi Ayu (CV ODIS, 2024)
This article discusses the role of Jakarta's restaurants in economic growth, focusing on job creation and culinary contributions. It explores crisis management, emphasising the importance of communication strategies for unexpected challenges. The SWOT analysis guides managers in aligning strengths with opportunities. Crisis communication involves organisational learning, ethical practices, prospective vision, and effective rhetoric. Management responsibilities in crises include risk assessment, plan development, transparent communication, media coordination, recovery, evaluation, and online information management.